Methodology for standardizing the normative model in centrales eléctricas de Norte de Santander – Grupo EPM. - Esguerra, Ingrid Y.; Lozano, Lizbeth G.; Villamizar, Luz D.; Acevedo Páez, Juan Camilo (AiBi Journal of Research, Administration and Engineering, 2016)
This document defines the methodology for standardizing the normative management model of CENS - Grupo EPM. To develop this methodology, a diagnosis of the current model was conducted using a structured questionnaire that determined the extent of the staff´s knowledge of policy management. Applied normative elements and implemented management systems were also analyzed, identifying those requirements that can be fulfilled through regulatory means. Finally, the current regulatory model of CENS was compared with the model of other electrical companies in Colombia and Mexico, highlighting flaws that require adaptations to the current regulatory model. Those adaptations will contribute to the successful execution of the processes and will help to meet the requirements of the management systems, all of which aim to strengthen the rules regarding the four regulatory elements discussed in Bussines Process Management